Safety, complications and clinical outcome after ultrasound‐guided paravertebral catheter insertion for rib fracture analgesia: a single‐centre retrospective observational study1. (27th January 2019) - Womack, J.; Pearson, J. D.; Walker, I. A.; Stephens, N. M.; Goodman, B. A.
Summary: Rib fractures are associated with significant morbidity and mortality. Ultrasound‐guided thoracic paravertebral catheter insertion has been described for the management of pain secondary to rib fractures. We conducted a retrospective observational study of all patients with rib fractures who had a paravertebral catheter inserted for analgesia provision over a 4‐year period. Data from the Trauma Audit and Research Network were used to compare patients with rib fractures who were managed with paravertebral catheters to those managed with systemic analgesia. A total of 314 consecutive paravertebral catheters were inserted in 290 patients. Five (1.9%) catheters were removed due to ineffective analgesia. Other minor complications occurred in three cases (0.96%). The proportion of rib fracture patients managed with paravertebral catheters increased from 31/200 (15.5%) in the first year of study to 81/168 (48.2%) in the fourth; over this time‐period the observed:predicted mortality ratio fell from 1.04 to 0.66. Proportional hazard regression with and without propensity score matching demonstrated a reduction in mortality associated with paravertebral catheter use, but this became statistically non‐significant when time‐dependent analysis was used. Paravertebral catheters are a safe and effective technique for rib fracture analgesia; however, our data were insufficient to demonstrate any improvement in mortality.